What landscape elements are needed for hospital healing spaces? Evidence from an empirical study of 10 compact hospitals - Guo, Haoxu; Zhou, Weiqiang; Lai, Wenbo; Yao, Lihao (Frontiers in Public Health, 2023)
Background Modern medical research shows that a rationally planned landscape environment helps patients recover. With the growing number of hospital patients and the tightening of per capita medical landscape land, the use of limited landscape resources to serve patients has become challenging. Methods This study focused on the landscape environment of 10 hospitals in Guangdong Province, China. Based on the KANO theoretical model, a survey questionnaire was designed and administered to 410 participants. The data were analyzed based on demand attributes, importance, sensitivity, and group differences. Results The maintenance requirements were the most important item in the sensitivity ranking. Furthermore, the analysis revealed that the users need a safe, quiet, and private environment, owing to their higher requirements, including visual healing, rehabilitation activities, shading and heat preservation, and medical escort. Moreover, adolescents and older adult patients have common and contradictory environmental needs. For example, the landscape environment should provide both an active space and a quiet rehabilitation environment. Conclusion This study evaluates how landscape resources can be better utilized from the perspective of the user and expands the theory of healing landscapes, which has practical implications for hospital renovation and landscape environment strategies.